Prevention and youth crime : is early intervention working? - Blyth, Maggie; Solomon, Enver (Researching criminal justice series., 2009)
The 2008 UK government Youth Crime Action Plan emphasises prevention and early intervention in different aspects of work with young people who offend or are considered to be 'at risk' of offending. Much of this approach includes targeted work with families and work to reduce the numbers of young people entering the youth justice system. This report takes a critical look at early intervention policies.